Penguatan Spiritualitas Siswa Melalui Mata Pelajaran PAI di Pesantren - Akhlak, Faza Karimatul; Padilah, Padilah (Prodi Pendidikan Keagamaan Islam, 2025)
The purpose of this study was to determine how Islamic boarding school-based Islamic Religious Education (PAI) improves spiritual intelligence. The study used a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that Islamic boarding school-based Islamic Religious Education (PAI) has been quite effective in improving spiritual intelligence, as students have developed aspects such as flexibility, coping with adversity, a quality of life strengthened by vision and values, avoidance of unnecessary harm, and a tendency to see the interconnectedness of various things.